Temporal reflexivity in journalism studies: Making sense of change in a more timely fashion. (May 2019) - Carlson, Matt; Lewis, Seth C
Journalism studies is a relatively young field trying to make sense of a relatively fast-moving scholarly object – news. The matter of time is emerging as a particularly vexing challenge: When so much seems to be changing, and so quickly, how are journalism studies researchers to discern meaningful developments as opposed to short-term ephemera? This essay argues for 'temporal reflexivity', a way of fostering critical judgment about whether some phenomenon is indeed a break from what came before, a continuation of what has existed, or some middle-ground mutation. Such thinking reveals how temporality is embedded within journalism studies, driving assumptions and incentives about how and what to research – as well as what not to research. In particular, we apply the lens of temporal reflexivity to discuss issues of time and attention across three key areas of concern for journalism studies' development as a field: first, the need for an analytical approach that balances change and stasis; second, the need to address issues of scale in which it is difficult to discern passing fads from deeper shifts that may lead to new institutional forms; and third, the need to understand the complicated and circular role of journalism education, both in reinforcing discourses of 'crisis' and 'innovation' and in lending stability to the boundaries of journalism as professionalized practice. In all, this essay opens up ways of considering the taken-for-granted temporal implications of research questions and pedagogical practices in journalism studies.